Morphological and mtDNA data reveal broader distribution of Alburnoides holciki (Teleostei: Leuciscidae) in inland waters of Central Asia - Levin, Boris; Thoni, Ryan; Artaev, Oleg; Bolotovskiy, Alexey; Levina, Marina; Rasulov, Azim; Mirzoev, Nuriddin; Simonov, Evgeniy (Zootaxa, 2019)
Alburnoides holciki was described from the Hari River basin, which was the only basin it was known from. Populations from the Amu Darya basin were previously recognized as A. eichwaldii or Alburnoides sp. Our study recognized specimens of Alburnoides from the Amu Darya basin as A. holciki based on morphological data and the COI barcode gene. The population from the Zeravshan basin showed some morphological differences compared to others but were similar in the COI gene and needs further investigation. New results extend the range of A. holciki for almost 1000 km from the Hari River to the upper Amu Darya tributaries in Tajikistan. The intraspecific genetic similarity in the COI gene between populations in the Hari and Amu Darya rivers supports the geographical hypothesis of a recent connection of these rivers.